Non-staged bilateral Globus Pallidus Internus deep brain stimulation lead revision using intraoperative MRI: a case report and literature review. (4th May 2021) - Hwang, Brian Y.; Mampre, David; Mills, Kelly; Courtney, Pamala; Kim, Min Jae; Butala, Ankur A.; Anderson, William S.
Abstract: Background: Deep brain stimulation (DBS) lead revision due to suboptimal therapy is common but there is no standardised protocol. We describe a novel technique using iMRI to perform concurrent new Globus Pallidus Internus (GPi) DBS lead implantation and old lead removal in a dystonia patient. Case-description: A 60-year-old woman with medication and neurotoxin-refractory isolated cervical dystonia underwent awake bilateral GPi DBS surgery with MER-guided lead implantation. She initially had a favourable response but later reported suboptimal benefit despite reprogramming. MRI demonstrated suboptimal lead placement and MRI-guided revision surgery under general anesthesia was planned. The goal was to place new leads superior and medial to the existing leads. Using a 1.5 T iMRI and the ClearPoint ® NeuroNavigation system, new leads were placed through the existing burr holes, into the new targets with radial errors < 0.08mm bilaterally without crossing the old leads. The old leads were then removed and the new leads connected to the existing pulse generator. The patient tolerated the procedure well and had improved side-effect profile at all contacts at 1-month follow-up. Conclusions: Non-staged iMRI-guided DBS revision surgery under general anesthesia is technically feasible and is an alternative strategy to a staged iMRI-guided revision surgery or an awake MER-guided revision surgery in select patients.